2009
DOI: 10.1016/j.virol.2009.08.029
|View full text |Cite
|
Sign up to set email alerts
|

A novel fusion protein domain III-capsid from dengue-2, in a highly aggregated form, induces a functional immune response and protection in mice

Abstract: Based on the immunogenicity of domain III from the Envelope protein of dengue virus as well as the proven protective capacity of the capsid antigen, we have designed a novel domain III-capsid chimeric protein with the goal of obtaining a molecule potentially able to induce both humoral and cell-mediated immunity (CMI). After expression of the recombinant gene in Escherichia coli, the domain III moiety retained its antigenicity as evaluated with anti-dengue sera. In order to explore alternatives for modulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 45 publications
0
31
1
1
Order By: Relevance
“…rified in this expression system. When it was presented as a particulate aggregate with random ODNs, it induced antiviral and neutralizing antibodies and CMI and conferred a significant level of protection in mice (26). Based on these features, we selected this molecule, in a particulate form with ODNs, to combine it with infective DEN-2 in a heterologous prime-boost regime of immunization in monkeys.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…rified in this expression system. When it was presented as a particulate aggregate with random ODNs, it induced antiviral and neutralizing antibodies and CMI and conferred a significant level of protection in mice (26). Based on these features, we selected this molecule, in a particulate form with ODNs, to combine it with infective DEN-2 in a heterologous prime-boost regime of immunization in monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant domain III-capsid protein comprises the domain III region of the envelope protein and the capsid protein, both from DEN-2. Previously, this protein in aggregated form was able to induce neutralizing antibodies, cell-mediated immunity (CMI), and protection against DEN-2 challenge in mice (26). In the present study, primed animals received one dose of the infective DEN-2 and were then vaccinated with the recombinant domain III-capsid protein.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Intriguingly, mice lacking the type I IFN receptor (IFNAR) on either LysM ϩ or CD11c ϩ cells were susceptible to disease but frequently recovered by 15 days postinfection (p.i. ); furthermore, immunization of either of these mice with a dengue virus EDIII-capsid (EDIIIC-2) subunit vaccine (30,31) induced high titers of dengue-specific neutralizing antibodies. Therefore, we have developed a novel model which has revealed that type I IFN receptor signaling in CD11c-and LysM-expressing cells has important and nonredundant roles in determining susceptibility to dengue.…”
mentioning
confidence: 99%